PET/CT in Multiple Myeloma: Beyond FDG - Matteucci, Federica; Paganelli, Giovanni; Martinelli, Giovanni; Cerchione, Claudio (Frontiers in Oncology, 2021)
Recent advances in the diagnosis and treatment of multiple myeloma (MM) have highlighted the importance of imaging methods, not only in the localization and extent of the disease but also in prognostic stratification and assessment of response to therapy. In this context, PET / CT, combining both morphological and functional information, is particularly useful in this pathology. The tracer mostly used is 18F-FDG, a glucose analog, which provides extremely accurate information with a sensitivity ranging from 80 to 100%. However, this tracer has some limitations, mostly related to the physiological uptake of FDG in the bone marrow and brain, which reduce its effectiveness. For this reason, some studies in the literature have evaluated the effectiveness of other PET tracers, which provide information on protein metabolism or the synthesis of metabolic plasma membranes, such as choline and methionine, as well as innovative radiopharmaceuticals, directed against receptors expressed by cells of myeloma, including tracers directed to the chemokine receptor. This review analyzes the characteristics and accuracy of non-FDG tracers in the management of patients with multiple myeloma.